Combined Use of Cognitive Behavioral Therapy (CBT) and Its Healing Impact on Drug Abusers Who Are Addicted to Drugs: A Scoping Review - Aeni, Nurul; Yosep, Iyus; Sriati, Aat (Indonesian Contemporary Nursing Journal (ICON Journal), 2024)
Aims: The aim of this study is to assist individuals in healing from addiction; it is essential to implement a combination of interventions, such as CBT, that are proven to be effective in treating drug abuse with a holistic approach that integrates psychological and social aspects for optimal results, according to empirical evidence. Methods: The search databases for this study were PubMed, ScienceDirect, and Google Scholar. Identify articles published in the last 10 years (2014-2024), Randomized Control Trials (RCTs), English and Indonesian, Full-Text, and Teenagers to the Elderly. Using the PRISMA flowchart, data extraction and scoping with keywords (English): "Drug Addict OR Substance Abuse AND Cognitive Behaviour Therapy AND Dependence OR Substance-Related Disorder" and keywords in the Indonesian language "Pecandu Narkoba OR Penyalahguna Zat AND Cognitive Behaviour Therapy AND Ketergantungan OR Gangguan Terkait Zat". Results: The study found eight articles that met the criteria, the main findings showed the use of Modified Cognitive Behavioral Therapy (M-CBT) in enhancing recovery motivation among cocaine-dependent individuals. Interventions such as galantamine, C-CBT, and computer-based CBT also show promise in reducing cocaine use. Additionally, combining CBT with contingency management (CM) facilitates changes in neural activity related to cognitive control. CBT paired with MET+ABI+ATTI and Female-Specific CBT (FS-CBT) effectively addresses alcohol use in adolescents and women.  Conclusion: Current study highlights various CBT approaches that can be combined, such as M-CBT for cocaine independence and computer-based CBT, as well as the combination of CBT with contingent management that influences neural activity related to cognitive control.